Pharmacological mechanisms of Euphorbia Pekinensis and Glycyrrhiza acting on hepatocellular carcinoma ascites: a preclinical study. (October 2016) - Mao, Xia; Yan, Chen; Li, Yuting; Lin, Ya; Guo, Qiuyan; Zhang, Yanqiong; Lin, Na
Abstract: Background: According to Chinese medicinal literature, Euphorbia Pekinensis and Glycyrrhiza should not be used together because of their antagonistic actions. However, increasing experimental and clinical evidence show that they exhibit synergistic or antagonistic actions when used together in different combinations. The aim of this study was to clarify the herbaceous compatibility of Euphorbia Pekinensis and Glycyrrhiza acting on hepatocellular carcinoma (HCC) ascites, which has not been fully elucidated. Methods: We initially undertook peritoneum transcriptomics profiling in 15 male Kunming mice (aged 4–6 weeks, 18–22 g weight) purchased from Charles River Laboratories (production license number SCXK 2012-0001, MA, USA). Mice were split into five groups: control, HCC ascites mouse model, Euphorbia Pekinensis alone, Euphorbia Pekinensis and Glycyrrhiza synergy, and Euphorbia Pekinensis and Glycyrrhiza antagonism treatment groups. Mice in Euphorbia Pekinensis alone, synergy, and antagonism groups were administrated daily with the combination of Euphorbia Pekinensis and Glycyrrhiza at the ratio of 1:0 (0·019 g/mL), 1:2 (0·058 g/mL), and 1:4 (0·097 g/mL), respectively, in a volume of 0·02 mL per gram of mice. Mice in control and HCC ascites mouse model groups received the same volume of normal saline (0·02 mL/g). We used the OneArray microarray platform, followed by screening of differentially expressed genes (DEGs) with the R package. After the interaction network of DEGs was constructed by STRING, we predicted the candidate targets implicated in the combinatory effects of the herbal pair by calculating network topological features and undertaking functional enrichment analysis, followed by a series of experimental validations. Findings: 2252 DEGs between the HCC ascites mouse model and control groups were considered as genes related to HCC ascites. We identified 86 genes related to the Euphorbia Pekinensis and Glycyrrhiza combination, including 25 genes that were upregulated in the HCC ascites mouse model compared with control, but downregulated with Euphorbia Pekinensis alone. 35 genes were upregulated in the HCC ascites mouse model compared with control, but downregulated after the synergy combination. Four genes were upregulated in both the HCC ascites mouse mode land antagonism combination compared with control. Ten genes were downregulated in the HCC ascites mouse model compared with control, but were upregulated after Euphorbia Pekinensis alone. 26 genes were downregulated in the HCC ascites mouse model compared with control, but upregulated after the synergy combination. One gene was downregulated in both the HCC ascites mouse model and antagonism combination compared with control. We constructed an interaction network using the links among genes related to HCC ascites, dysregulated genes after the treatment of Euphorbia Pekinensis and Glycyrrhiza combination, and known therapeutic target genes for ascites. On the basis of nodes' degree, closeness, betweenness, and k-coreness, the Frk-Arhgdib-Inpp5d-Avpr2-Aqp4 axis was shown to be a candidate target of the Euphorbia Pekinensis and Glycyrrhiza combination acting on HCC ascites. Both qualitative PCR and western blot analyses verified the regulatory effects of the Euphorbia Pekinensis and Glycyrrhiza pair on the candidate target. Interpretation: Our data provide evidence that the different combination designs of Euphorbia Pekinensis and Glycyrrhiza can lead to synergistic or antagonistic effects on HCC ascites via regulation of the Frk-Arhgdib-Inpp5d-Avpr2-Aqp4 signal axis. These findings suggest that global gene expression profiling combined with network analysis and experimental validations can offer an effective way to understand the pharmacological mechanisms of traditional Chinese medicine prescriptions. Funding: The National Basic Research Program of China (973 Program) (2011CB505300, 2011CB505305), the National Natural Science Foundation of China (81303153), Beijing Nova program (Z1511000003150126), and the Prospective Study Platform Project of Institute of Chinese Materia Medica, China Academy of Chinese Medical Sciences (QZPT002).